THU0056 EFFECTS OF CX3CL1 INHIBITION ON MURINE BLEOMYCIN-INDUCED INTERSTITIAL PNEUMONIA. (June 2019) - Yamada, Soichi; Miyoshi, Shion; Kusunoki, Natsuko; Sato, Hiroshi; Kuboi, Yoshikazu; Hoshino-Negishi, Kana; Ishii, Naoto; Imai, Toshio; Mikami, Tetsuo; Nakano, Hiroyasu; Kawai, Shinichi; Nanki, Toshihiro
Abstract : Background: Pathological findings of interstitial pneumonia (IP) reveal the accumulation of inflammatory cells and proliferation of fibroblasts in lung tissue. Although a treatment has not yet been established for IP, particularly for IP with collagen diseases, chemokines may play a role in the pathogenesis of IP for inflammatory cell infiltration. We previously reported that chemokine (C-X3-C motif) ligand 1 (CX3CL1, also known as fractalkine) has potential as a therapeutic target for rheumatoid arthritis (RA). 1, 2, 3 Humanized anti-human CX3CL1 monoclonal antibody (mAb) is currently undergoing clinical trials for RA. 4 Objectives: In the present study, we examined the therapeutic effects of CX3CL1 blockade in a murine model of IP. Methods: Bleomycin (BLM)-induced IP was developed by the intratracheal administration of BLM to C57BL/6 mice. The murine lung was stained with hematoxylin and eosin, and the expression of CX3CL1 and CX3CR1, a receptor for CX3CL1, was analyzed by immunohistochemistry. Mice were treated with anti-CX3CL1 mAb for 2 weeks. Collagen eluted from the lung was quantified using the Sircol TM Collagen Assay. The expression of CX3CL1 and CX3CR1 by mouse lung fibroblasts (MLFs) was examined with quantitative RT-PCR and Western blotting, respectively. Cell movement was investigated using the scrape motility assay. Results: The expression of CX3CL1 and CX3CR1 was upregulated in BLM-induced IP. The treatment with anti-CX3CL1 mAb did not significantly alter inflammatory cell infiltration. However, collagen in the lung was decreased by the treatment with anti-CX3CL1 mAb. Stimulation with CX3CL1 did not alter the in vitro production of collagen by MLFs, but significantly enhanced cell movement. Conclusion: CX3CL1 may be involved in increasing collagen in IP and the cell movement of MLFs. The present results suggest that CX3CL1 plays an important role in fibrosis in IP. References: [1] Nanki T, et al. Inhibition of fractalkine ameliorates murine collagen-induced arthritis. J Immunol. 2004;173(11):7010-6. [2] Nanki T, et al. Migration of CX3CR1-positive T cells producing type 1 cytokines and cytotoxic molecules into the synovium of patients with rheumatoid arthritis. Arthritis Rheum. 2002;46(11):2878-83. [3] Nanki T, et al. Fractalkine/CX3CL1 in rheumatoid arthritis. Mod Rheumatol. 2017 May;27(3):392-397. [4] Tanaka Y, et al. Safety, pharmacokinetics, and efficacy of E6011, an antifractalkine monoclonal antibody, in a first-in-patient phase 1/2 study on rheumatoid arthritis. Modern rheumatology. 2018;28(1):58-65. Disclosure of Interests: Soichi Yamada: None declared, Shion Miyoshi: None declared, Natsuko Kusunoki: None declared, Hiroshi Sato: None declared, Yoshikazu Kuboi Shareholder of: Eisai Co., Ltd., Employee of: KAN Research Institute, Inc. (subsidiary of Eisai Co., Ltd.), Kana Hoshino-Negishi Shareholder of: Eisai Co., Ltd., Employee of: KAN Research Institute, Inc. (subsidiary of Eisai Co., Ltd.), NAOTO ISHII Shareholder of: Eisai Co., Ltd., Employee of: KAN Research Institute, Inc. (subsidiary of Eisai Co., Ltd.), Toshio Imai Shareholder of: Eisai Co., Ltd., Employee of: KAN Research Institute, Inc. (subsidiary of Eisai Co., Ltd.), Tetsuo Mikami Speakers bureau: EA Pharma, Hiroyasu Nakano: None declared, Shinichi Kawai Grant/research support from: Nippon Zoki, Chugai, Ono, Ayumi, Hisamitu, Eisai, Japan Tobacco, Nippon Kayaku, Daiichi Sankyo, Astellas, Yutoku, and Mitsubishi Tanabe, Consultant for: Santen, Japan Tobacco, Speakers bureau: Ayumi, Chugai, Ono, Astellas, Pfizer, Celltrion, Toshihiro Nanki Grant/research support from: Chugai, Eisai, Takeda, Teijin, Eli Lilly, Bristol-Myers, AbbVie, Ono, Novartis, Asahikasei, Mitsubishi-Tanabe, Astellas, Ayumi, Pfizer, Daiichi Sankyo, Shionogi, Sanofi, Nippon Kayaku, Yutoku, Actelion, UCB, Bayer, Nihon Pharmaceutical., Consultant for: UCB, Eisai, Chugai, Ono, Gilead., Speakers bureau: Mitsubishi-Tanabe, Chugai, Eisai, Takeda, Astellas, Janssen, Eli Lilly, Ayumi, Pfizer, Asahikasei, Sanofi, Daiichi Sankyo, Otsuka, AbbVie, Ono, Teijin, Nippon Kayaku, UCB.